Pengaruh Metode Demonstrasi terhadap Motivasi dan Hasil Belajar Siswa Kelas XI SMA - Onny, Fariha (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
The problem of Biology learning at SMA Negeri 11 Semarang, namely that learning still uses conventional methods, where teachers talk more, ask questions and tell stories to inform all the facts and concepts of learning, the low number of positive activities that students remember is due to the learning techniques used by The teacher does not facilitate students to be more active in receiving the material presented by the teacher. This affects the low motivation and learning outcomes of students. To overcome this problem, the demonstration method is used. This research is an experimental research with a non-equivalent groups pretest-posttest design which aims to determine the effect of the demonstration method on the motivation and learning outcomes of class XI students at SMA Negeri 11 Semarang. The population of this study was all class XI SMA Negeri 11 Semarang with a total of 141 students. Sampling was carried out using a purposive sampling technique with class XIF as the experimental class and class XIE as the control class. The independent variable in this research is the demonstration method and the dependent variable, namely motivation and student learning outcomes. Data on student motivation results were analyzed descriptively and results were obtained at the first meeting with a percentage of 50% and categorized as low, then at the second meeting with a percentage of 62.5% categorized as quite high, because there was an increase at each meeting, it was concluded that the use of the demonstration method could improve Learning motivation of class XIF students at SMA Negeri 11 Semarang. Data on student learning outcomes were analyzed using a two-party t-test with the polled variance t-test formula. At a significance level of 5%, the degrees of freedom (dk=43) obtained tcount > ttable (3.280 > 2.014), so Ha is accepted and H0 is rejected. So from the results of the analysis of learning outcomes it can be concluded that the use of the demonstration method influences the learning outcomes of class XI students at SMA Negeri 11 Semarang.